2016
DOI: 10.14348/molcells.2016.0164
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Glucocorticoid Receptor-Mediated Regulation of Glutathione Peroxidase 3 in Lung Cancer Cells

Abstract: Glutathione peroxidase 3 (GPx3), an antioxidant enzyme, acts as a modulator of redox signaling, has immunomodulatory function, and catalyzes the detoxification of reactive oxygen species (ROS). GPx3 has been identified as a tumor suppressor in many cancers. Although hyper-methylation of the GPx3 promoter has been shown to down-regulate its expression, other mechanisms by which GPx3 expression is regulated have not been reported. The aim of this study was to further elucidate the mechanisms of GPx3 regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Plasma GPx (GPx3) is the most important selenoenzyme involved in deactivating ROS, acting via thioredoxin and glutathione as reduction co-substrates [ 21 , 26 ]. Recently, we demonstrated glucocorticoid receptor-mediated upregulation of GPx3 in lung cancer cells [ 27 ]. Downregulation of GPx3 via promoter hypermethylation occurs in many types of human cancer, suggesting that GPx3 acts as a tumor suppressor [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma GPx (GPx3) is the most important selenoenzyme involved in deactivating ROS, acting via thioredoxin and glutathione as reduction co-substrates [ 21 , 26 ]. Recently, we demonstrated glucocorticoid receptor-mediated upregulation of GPx3 in lung cancer cells [ 27 ]. Downregulation of GPx3 via promoter hypermethylation occurs in many types of human cancer, suggesting that GPx3 acts as a tumor suppressor [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of GPX3 is regulated by hypermethylation and glucocorticoid receptor-mediated mechanisms [8]. In addition, GPX3 is a direct estrogen receptor alpha target gene in white AT [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GPX3 is a direct estrogen receptor alpha target gene in white AT [9]. GPX3 acts as a modulator of redox signaling, has immunomodulatory function, catalyzes the detoxification of ROS, and has been identified as a tumor suppressor in different types of cancer [6, 8]. Oxidative stress contributes to AT dysfunction in obesity [10, 11], hence GPX3 may play a crucial role as local defense mechanism, particularly in obesity [5, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported that when compared with normal cells, cancer cells presented with changed metabolism, and increased ROS production . However, GPX3, an antioxidant enzyme, can induce the detoxification of ROS . GPX3 could detoxify ROS thus modulating redox‐mediated signals, by which GPX3 impedes lung cancer cell proliferation .…”
Section: Discussionmentioning
confidence: 82%